Effects of vitamin K deficiency and its mechanisms in vertebrate's early development: zebrafish as a model - Granadeiro, Luís Carlos Serrachino (2017)
Disertação de mestrado, Ciências Biomédicas, Departamento de Ciências Biomédicas e Medicina, Universidade do Algarve, 2015